Anomalously Deep BSR Related to a Transient State of the Gas Hydrate System in the Western Black Sea. (23rd January 2019) - Ker, S.; Thomas, Y.; Riboulot, V.; Sultan, N.; Bernard, C.; Scalabrin, C.; Ion, G.; Marsset, B.
Abstract: A comprehensive characterization of gas hydrate system offshore the western Black Sea was performed through an integrated analysis of geophysical data. We detected the bottom‐simulating reflector (BSR), which marks, in this area, the base of gas hydrate stability. The observed BSR depth does not fit the theoretical steady state base of gas hydrate stability zone (BGHSZ). We show that the disparity between the BSR and predicted BGHSZ is the result of a transient state of the hydrate system due to the ongoing reequilibrium since the Last Glacial Maximum. When gas hydrates are brought outside the stability zone due to changes in temperature and sea level, their dissociation generates an increase in interstitial pore pressure. This process is favorable to the recrystallization of gas hydrates and delays the upward migration of the hydrate stability zone explaining the anomalously deep BSR. The BSR depth, which is commonly used to derive geothermal gradient values by assuming steady state conditions, is used here to derive the maximum excess pore pressure at the BGHSZ. Derived excess pore pressure values of 1–2 MPa are probably the result of the low permeability of hydrate‐bearing sediments. Higher pore pressure values derived at the location of a fault system could cause hydrofracturing enabling the free gas to cross the gas hydrate stability zone and emerge at the seafloor, forming the flares observed in close vicinity to where the shallow gas hydrates were sampled. Key Points: There is a discrepancy between observed BSR depth and theoretical steady state base of gas hydrate stability zone The transient state of the hydrate system is due to excess pore pressure related to hydrate dissociation BSR depth is used to derive maximum excess pore pressure at the base of the gas hydrate stability zone